Association of markers of patellofemoral maltracking to cartilage damage and bone marrow lesions on MRI: Data from the 2016 Olympic Games of Rio De Janeiro. (2021) - Jarraya, Mohamed; Roemer, Frank W.; Engebretsen, Lars; Kompel, Andrew J.; Small, Kirstin M.; Smith, Stacy E.; Guermazi, Ali
Abstract: Background: Patellofemoral joint (PFJ) disease is a common ailment in elite athletes. Our aim is to report the frequency of superolateral Hoffa's fat pad (SHFP) edema, and PFJ cartilage damage and bone marrow lesions (BML), among Olympian athletes, and to study the association between measurements of trochlear morphology and vertical patellar position and a) PFJ cartilage damage or BML, and b) SHFP edema. Methods: All knee MRI, performed in the Olympic Village and polyclinics, of participating athletes in the 2016 Olympic Games of Rio de Janeiro were included. MRI were scored for PFJ cartilage damage and BML, and SHFP edema. Trochlear morphology measurements included sulcus angle, trochlear angle, lateral trochlear inclination, and medial trochlear inclination. Insall-Salvati ratio was also assessed. Results: One hundred twenty-one knee MRIs were included (62 female, 51.2 %). The highest frequencies of PFJ cartilage damage, combination of PFJ cartilage damage and BML, and SHFP edema were found among Beach Volleyball and Volleyball athletes. SHFP edema was more common among female compared to male Olympian athletes. We found no statistically significant associations between different measurements of trochlear morphology/vertical patellar position, and 1. SHFP edema, and 2. PFJ cartilage damage/BML. Conclusion: SHFP edema and the combination of PFJ cartilage damage and BML are highly frequent among Olympic athletes especially those competing in Beach volleyball and Volleyball. SHFP edema is more common among female athletes. Further studies are needed to determine whether PFJ cartilage damage has a stronger association to sports disciplines rather than trochlear morphology.